Effects of the carrier frequency of interferential current on pain modulation and central hypersensitivity in people with chronic nonspecific low back pain: A randomized placebo‐controlled trial. (6th May 2016) - Corrêa, J.B.; Costa, L.O.P.; Oliveira, N.T.B.; Lima, W.P.; Sluka, K.A.; Liebano, R.E.
Abstract: Background: Interferential current (IFC) is commonly used for pain relief, but the effects of carrier frequency of the current and its action on pain mechanisms remain unclear. This randomized placebo‐controlled trial tested the effects of IFC in people with chronic nonspecific low back pain. Methods: One hundred and fifty participants were randomly allocated into three groups: 1 kHz, 4 kHz and placebo. The primary outcomes were pain intensity at rest in the first session (immediate effect of the IFC), after 12 sessions, 4 months after randomization (follow‐up) and during movement (first and last session). The secondary outcomes were disability, global perceived effect, functional performance, discomfort caused by the IFC, use of analgesics and physiological measures of pain. Results: Only during the first session, there was a significant decrease in pain intensity in the active groups. However, there were no differences in the improvement of pain at rest or during movement in the active groups compared to the placebo group in the remaining sessions. The frequency use of analgesics was significantly decreased in the active groups. For pain physiology measures, there was a significant increase in pressure pain thresholds in both active groups compared to the placebo group and a reduction in the temporal summation in the 1 kHz group compared to the other groups. Conclusions: These results suggest that although the IFC has changed some physiological mechanisms of pain and showed decrease frequency use of pain medication, there was no change in the primary aim, pain intensity. What does this study add?: The interferential current (IFC) presented advantages in the physiological measures of pain and showed decrease frequency use of pain medication. Future studies should investigate analgesic intake with IFC treatment.